Mucosal bacterial immunotherapy with MV130 highly reduces the need of tonsillectomy in adults with recurrent tonsillitis - Luis-Amando García González; Federico Arrutia Díez (Taylor & Francis Group, 2019)
Recurrent tonsillitis in adults is a common ENT disease. The current standard treatment is tonsillectomy. However, continuous prophylaxis with antibiotics has been prescribed in order to avoid tonsillectomy. The objective was to evaluate if the bacterial immunotherapy (Bactek MV130) together with the prophylactic antibiotic therapy can produce clinical improvement and to avoid the tonsillectomy. Material and methods The medical records of 88 patients with recurrent tonsillitis were reviewed. Sixty-six were treated during 3 months with a course of antibiotics and 22 received, in addition to the antibiotics, immunotherapy with Bactek MV130 during this Globally, 53 (60%) patients had clinical improvement and 35 were tonsillectomized. In the The group of patients who received only antibiotic, 35 (53%) avoided tonsillectomy and 31 (47%) did not. In the group that, in addition to antibiotics, were treated with Bactek MV130, 18 patients (82%) experi- enced clinical improvement avoiding tonsillectomy and 4 (18%) didn't improve and the tonsils were surgically removed. The difference between both groups was significant (P = 0.023).he results obtained in this evaluation support this combined treatment as an effective strategy to reduce the need of tonsillectomy.